The effect of different energy and nitrogen sources on in vitro fibre digestion and gas production kinetics of high and low quality forages. - Neethling, Kathleen Elizabeth (Stellenbosch : Stellenbosch University, 2016)
Thesis (MScAgric)--Stellenbosch University, 2016.